1952
DOI: 10.1139/cjms52-043
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Zinc in the Human Prostate Gland

Abstract: The prostate gland contains a higher concentration of zinc than any soft tissue in the human body previously investigated. In an extensive series of analyses Eggleton found the highest concentration in liver (245 μgm. Zn per gm. dry weight), whereas the mean zinc content of all our specimens of human prostate was 682 ± 70 μgm. per gm. dry weight. Carcinomatous prostates contained much less zinc than normal glands, and the amount of zinc in any given prostate was directly related to the proportion of alveolar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
3

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 0 publications
5
61
0
3
Order By: Relevance
“…In the rat prostate, high MT concentration was seen in the lateral prostate, which has a high zinc concentration (Gunn and Gould 1957;Muntzing et al 1977;Bataineh et al 1986;Umeyama et al 1987;Suzuki et al 1991). In human prostate, a high MT concentration in tissues of the peripheral zone, which also exhibit high zinc concentration has been described (Mawson and Fisher 1952;Suzuki et al 1991). MT secreted into the prostatic fluid by prostatic epithelial cells we have recently found using radioimmunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat prostate, high MT concentration was seen in the lateral prostate, which has a high zinc concentration (Gunn and Gould 1957;Muntzing et al 1977;Bataineh et al 1986;Umeyama et al 1987;Suzuki et al 1991). In human prostate, a high MT concentration in tissues of the peripheral zone, which also exhibit high zinc concentration has been described (Mawson and Fisher 1952;Suzuki et al 1991). MT secreted into the prostatic fluid by prostatic epithelial cells we have recently found using radioimmunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc concentration is high in prostatic tissue and fluid (Mawson and Fischer 1952a;Gyorkey et al 1967 ;Anderson and Fair 1976;Ogunlewe et al 1989), and the concentration of zinc has been found to affect male infertility (Anderson et al 1976). This shows MT of the prostate binds to zinc.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of zinc is high in prostatic tissues and fluids (Mawson and Fischer 1952a;Gyorkey et al 1967; Anderson and Fair 1976;Ogunlewe and Osegbe 1989). We reported the localization of MT in the rat and human prostate by immunohistochemistry (Umeyama et al 1987; Suzuki et al 1991) The essential role of MT in the prostate gland remains unclear.…”
mentioning
confidence: 88%
“…There is good evidence that zinc may contribute to prostate cancer incidence. Total zinc levels in the prostate are 10 times higher than in other soft tissues (Mawson and Fisher, 1952). Uptake of zinc via a membrane transporter into prostatic epithelial cells is under the control of hormones (testosterone, prolactin) (Costello et al, 1999).…”
Section: Zincmentioning
confidence: 99%